Ag Nanoparticles Decorated TiO2 Thin Films with Enhanced Photocatalytic Activity. Issue 14 (28th January 2019) - Veziroglu, Salih; Ghori, Muhammad Zubair; Obermann, Anna‐Lena; Röder, Katharina; Polonskyi, Oleksandr; Strunskus, Thomas; Faupel, Franz; Aktas, Oral Cenk
Abstract : A highly photocatalytic Ag/TiO2 thin film is prepared by the photocatalytic deposition of Ag nanoparticles (NPs) on reactive sputtered columnar TiO2 structures. By altering the ultra‐violet (UV) exposure time, the authors control the morphology and surface coverage of deposited Ag NPs. While a surface coverage of 1–4% (by Ag NPs) leads to a significant increase in the photocatalytic activity, depositing more Ag NPs yield a decrease in the photocatalytic performance (lower than that of bare TiO2 ). This may arise due to the blocking of UV light incoming to the TiO2 by the formation continuous network of Ag clusters on the surface. Such highly interconnected Ag clusters might also trigger the recombination of electron‐hole pairs. After five consecutive photocatalysis tests, the Ag (1 min)/TiO2 thin film remains intact. Abstract : Photocatalytic deposition of Ag nanoparticles (NPs) on TiO2 micro‐ and nanoparticles has been shown by various research groups. Nevertheless, in case of such immobilized TiO2 particles a high‐intensity UV irradiation is needed for generating sufficient electrons to reduce Ag + ions. Such a high‐intensity UV irradiation causes non‐controlled reduction of Ag + ions to Ag NPs. By using a highly photocatalytic active TiO2 thin film, a low‐intensity UV irradiation leads a very controlled deposition of Ag NPs on TiO2 thin film surface. This enables a significant enhancement in photocatalytic performance.